Structural modifications as tools in mechanistic studies of the cleavage of RNA phosphodiester linkages - Lönnberg Harri (WILEY-V C H VERLAG GMBH, 2025)
The cleavage of RNA phosphodiester bonds by RNase A and hammerhead ribozyme at neutral pH fundamentally differs from the spontaneous reactions of these bonds under the same conditions. While the predominant spontaneous reaction is isomerization of the 3',5'-phosphodiester linkages to their 2',5'-counterparts, this reaction has never been reported to compete with the enzymatic cleavage reaction, not even as a minor side reaction. Comparative kinetic measurements with structurally modified di-nucleoside monophosphates and oligomeric phosphodiesters have played an important role in clarification of mechanistic details of the buffer-independent and buffer-catalyzed reactions. More recently, heavy atom isotope effects and theoretical calculations have refined the picture. The primary aim of all these studies has been to form a solid basis for mechanistic analyses of the action of more complicated catalytic machineries. In other words, to contribute to conception of a plausible unified picture of RNA cleavage by biocatalysts, such as RNAse A, hammerhead ribozyme and DNAzymes. In addition, structurally modified trinucleoside monophosphates as transition state models for Group I and II introns have clarified some features of the action of large ribozymes.